Legal Personhood, Cossío's Thought, and Contemporary Doctrine - Fernández Sessarego, Carlos (1983)
This article examines the egological theory of law proposed by Carlos Cossio, its impact on Latin American legal thought and the conception of the legal person in law. The author begins by highlighting the originality and diffusion of Cossio's work, and then addresses his conception of the ‘legal person’. This perspective is contrasted with the theories of Savigny, Gierke and Kelsen, which he criticises for the disconnection they establish between man and law. In contrast to these positions, the author proposes a vision based on legal experience, existential philosophy and phenomenology. In this framework, the egological theory is presented as an alternative to the explanations that resort to fictions or autonomies to explain legal personality. It also discusses contemporary trends in the theory of personhood, influenced by analytical philosophy, and the contributions of Italian jurists who advocate open-ended constructions that reflect the plurality of situations in legal experience. From the above, the author concludes that the legal person is an expression of normativity that refers to the regulation of human relations, and that the current approach tends to be more open and flexible, capable of adapting to the complexity of social reality.